Draft Five Year Plan-Orissa 1978-83 * Vol. II - Planning Commission (Planning Commission, 1978)
Outlays and Expenditure Outlays and Expenditure Minor Head wise Selected Targets and Achievements Minimum Needs Programme Centrally Sponsored Schemes Financial Outlays under Tribal Sub-Plan. T—Sub-Plan Tribal Sub-Plan Targets and Achievements—T—Sub-Plan Direct Employment—EMP.
Government of Orissa, Planning and Co-ordination Department